Relación de inteligencia emocional con rendimiento académico en estudiantes del primer y sexto año de medicina de la Universidad Nacional de Trujillo - Asmat Vargas, Diana Elizabeth (2018)
The objective of this study was to determine the relationship of emotional intelligence and academic performance of students of the first and sixth year of Medicine at the Universidad Nacional de Trujillo. It was an observational, descriptive, correlational, cross-sectional and prospective study. A total of 161 students from the Faculty of Medicine of the Universidad Nacional de Trujillo were studied in the 2015 academic year, 85 of the first year and 76 of the sixth year, in which the Emotional Inventory of Baron ICE was applied, which allowed knowing their emotional intelligence and obtaining the annual weighted averages. Nonparametric tests of the Mann-Whitney U for independent samples, Spermann's Rho correlation coefficients and Chi-square were used in the statistical software package IMB SPSS Statistics 24. The first and sixth year students have adequate emotional intelligence. The academic performance is significantly higher in the sixth year. In both groups there is a very low negative correlation, and not significant. It was concluded that there is no significant difference in the very low correlation of emotional intelligence and academic performance of the students of the first and sixth year of Medicine of the Universidad Nacional de Trujillo